Raw mass spectrometric data to dissolved organic matter molecular composition data of exemplary water masses resolved by online LC-FT-ICR-MS - Fabian Moye; Marlo Bareth; Boris P Koch; Jan Tebben; Tilmann Harder (PANGAEA, 2025)
The unique chromatographic behaviour of DOM was investigated on three exemplary water samples representing coastal DOM, oceanic surface DOM and oceanic refractory DOM. Weddell Sea surface (30 m depth, oceanic surface DOM) and deep water (1356 m depth, refractory DOM) was sampled with a rosette sampler on RV Polarstern during ANT XXII/2 (station PS67/006-130, latitude -67.5633, longitude -55.3448) and are described elsewhere (El Naggar et al., 2007; Koch et al., 2008). Coastal DOM is routinely extracted from southern North Sea (latitude 54.1447, longitude 7.8711) and used as an in-house laboratory standard. Mass spectra were obtained with liquid chromatography coupled to a Fourier-transform ion cyclotron resonance mass spectrometer (LC-FT-ICR-MS) with negative electrospray ionisation. A 7 Tesla scimaX MRMS system (Bruker Daltonics GmbH & Co. KG, Bremen, Germany) was coupled to an ultra-performance liquid chromatography system (UPLC, Elute LC, Bruker Daltonics GmbH & Co. KG, Bremen, Germany). Reversed phase chromatography was done with a C18 column (Waters AQUITY 2 x 100 mm, 1.7 μm) column at 0.3 mL min 1 and a linear gradient: A (ultrapure water, 4 mmol L 1 ammonium formate) 2 min: 99 %, 11 min: 0 %, 14.9 min: 99 %; B (MeOH, 4 mmol L 1 ammonium formate) 2 min: 1 %, 11 min: 100 %, 14.5 min 100 %, 14.9 min 1 %. The exact mass lists and intensities of the 1.1 min binned scans were exported with the DataAnalysis 5.3 software package (Bruker Daltonics GmbH & Co. KG, Bremen, Germany).
In: Moye, F et al. (2025): Dissolved organic matter molecular composition data of exemplary marine water masses resolved by online LC-MS [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.974712